The Impact of Environmental Uncertainty on Supply Chain Risks in Vietnamese Textile Enterprises - Cuong, Nguyen Le; Lam, Nguyen Xuan; Khanh, Lam Cao (Business and Economic Research, 2024)
The Vietnamese textile industry is facing significant development opportunities from the Free Trade Agreements that have been signed, which will bring potential for export expansion to major markets worldwide. Through the process of researching the supply chain status of the textile industry, the author recognizes the influence of environmental uncertainty on the operational efficiency of Vietnamese textile enterprises. Based on theoretical foundations, research models, and research results, the author draws several conclusions. The research results indicate the impact of environmental uncertainty on supply chain risks in Vietnamese textile enterprises. It also highlights the importance of adopting flexible measures in the supply chain to mitigate risks for textile enterprises.